Different doses of dual orexin receptor antagonists in primary insomnia: a Bayesian network analysis - Xue, Tao; Wu, Xin; Li, Jiaxuan; Chen, Shujun; Wang, Zilan; Tan, Xin; Wang, Zhong; Zhang, Jianguo (Frontiers in Pharmacology, 2023)
Background: Systematic comparisons of the doses of the Food and Drug Administration (FDA)-approved dual orexin receptor antagonists (DORAs) for people with insomnia are limited. Methods: PubMed, Embase, Cochrane Library, and Clinicaltrials.gov were systematically searched to identify relevant studies published before October 31, 2022. We assessed the certainty of evidence using the confidence in network meta-analysis (CINeMA) framework. Results: We pooled 7257 participants from 9 randomized controlled trials (RCTs). Moderate to high certainty evidence demonstrated suvorexant (20 and 40 mg) and daridorexant (10 and 50 mg) as the most effective in latency to persistent sleep (LPS) reduction. Lemborexant at 5 and 10 mg was the most effective in subjective sleep onset time (sTSO) reduction. For wake time after sleep onset (WASO), all drugs except daridorexant 5 mg were more effective than placebo. Lemborexant 5 mg was among the best in subjective WASO (sWASO) (moderate to high certainty) and had the highest surface under the curve ranking area (SUCRA) values for sWASO (100%). For total sleep time (TST), suvorexant and daridorexant, except the respective minimum doses, were more effective than placebo, while suvorexant 40 mg and lemborexant 10 mg may have been the most effective for subjective TST (sTST) (low to very low certainty). Suvorexant 40 mg (RR 1.09), suvorexant 80 mg (RR 1.65), and daridorexant 25 mg (RR 1.16) showed a higher safety risk than placebo. Conclusion: Suvorexant 20 mg, lemborexant 5 mg, lemborexant 10 mg, and daridorexant 50 mg represent suitable approaches for insomnia. Trial Registration Information: PROSPERO (CRD42022362655)